Panggilan Gereja di Era Digital:: Menjawab Kebutuhan Jemaat dengan Pendekatan Kurikulum Maria Harris - Sirongo, Binamonika; Essuy K. A Pit’ay; Degunias Ton; Dyoys Anneke Rantung; Stepanus Daniel (MANTHANO: Jurnal Pendidikan Kristen, 2025)
Abstract: This study examines the relevance and implementation of Maria Harris's curriculum as a church's response to the challenges of ministry in the digital age. Maria Harris's curriculum, which focuses on five dimensions—didaskē (teaching), leitourgia (liturgy), koinonia (fellowship), kerygma (proclamation), and diakonia (service)—is considered relevant for holistically shaping the character, faith, and spirituality of the congregation. Using a qualitative approach with a literature study method, this article analyzes existing literature regarding the application of these five curriculum dimensions in digital contexts, such as online worship, digital biblical classes, and social media-based ministry platforms. The research findings indicate that integrating digital technology with the dimensions of the Maria Harris curriculum can significantly enhance the church's effectiveness in meeting the spiritual and existential needs of modern congregations. This article contributes to the theoretical and practical understanding of the church's adaptation in the digital age through a structured curriculum framework. Abstrak: Penelitian ini mengkaji relevansi dan implementasi kurikulum Maria Harris sebagai respons gereja terhadap tantangan pelayanan di era digital. Kurikulum Maria Harris, yang berfokus pada lima dimensi—didaskē (pengajaran), leitourgia (liturgi), koinonia (persekutuan), kerygma (pewartaan), dan diakonia (pelayanan)—dipandang relevan untuk membentuk karakter, iman, dan spiritualitas jemaat secara holistik. Menggunakan pendekatan kualitatif dengan metode studi pustaka, artikel ini menganalisis literatur terkait penerapan kelima dimensi kurikulum tersebut dalam konteks digital, seperti ibadah daring, kelas biblika, dan platform pelayanan berbasis media sosial. Hasil penelitian menunjukkan bahwa integrasi teknologi digital dengan dimensi kurikulum Maria Harris dapat secara signifikan meningkatkan efektivitas gereja dalam memenuhi kebutuhan rohani dan eksistensial jemaat modern. Artikel ini berkontribusi pada pemahaman teoretis dan praktis mengenai adaptasi gereja di era digital melalui kerangka kurikulum yang terstruktur.